Mixed apocrine adenocarcinoma of the tail in a cow - Tessele, Bianca; Rissi, Daniel R.; Langohr, Ingeborg M.; Vielmo, Andréia; Barros, Claudio S. L. (Brazilian Journal of Veterinary Pathology, 2015)
This report describes an uncommon case of neoplasm in domesticated animals, mixed apocrine adenocarcinoma (MAA). A cutaneous mass from the tail and anal region of an adult cow was detected during the routine antemortem examination of cattle in a slaughterhouse. The mass was ulcerated, firm, measured 23 x 20 x 20 cm and weighed 10 Kg. There were extensive areas of hemorrhage and necrosis admixed with irregular islands of bone. Histopathological examination revealed multiple cysts with papillary projections into lumen. Periodic acid-Schiff (PAS) reaction revealed amorphous eosinophilic secretory material into luminal spaces and on the apical surface of neoplastic cells. Immunohistochemical investigation revealed strong cytoplasmic immunostaining of the epithelial neoplastic cells for cytokeratin 19 (CK19) and strong positive immunostaining of the myoepithelial cells for smooth muscle actin (αSMA) and S-100 protein. These gross and histopathological findings observed during this study led to a final diagnosis of MAA.